Experimental and numerical activity on a prototype ejector chiller. (August 2020) - Mahmoudian, J; Mazzelli, F; Milazzo, A; Rocchetti, A
Abstract: Research activity on ejectors is ongoing at the University of Florence since the late nineties. The most important achievement is a 40 kW ejector chiller designed according to the "CRMC" criterion. The experimentally validated CFD simulations have given some hints about some possible improvements, i.e. refine the surface finish of the ejector, study the effect of heat transfer and improve the final part of the diffuser, which in its present shape does not produce a measurable compression. The prototype has been recently filled with low-GWP refrigerant R1233zd, as a drop-in replacement of previously used R245fa. Both fluids are "dry-expanding" and hence significantly easier to model in CFD simulations. Synthetic low-GWP refrigerants may be an option for ejector chillers, due to their ability to reach below-zero temperature and high volumetric refrigerant capacity. Some lessons learned with synthetic refrigerants can be transferred to the project of a steam ejector chiller, which remains one of our future targets. Herein we resume the principal findings gathered by means of experimental and numerical activity on our prototype and propose a few ideas for the future research.